Plasmodium falciparum Malaria Complicated by Symmetrical Peripheral Gangrene, Bowel Ischemia, Repeated Candidemia, and Bacteraemia - Emeline Masse; Philippe Hantson (Case Reports in Medicine)
A 63-year-old Caucasian woman developed severe Plasmodium falciparum malaria when travelling back from Cameroun. No antimalarial chemoprophylaxis had been observed. The patient was immediately admitted to the intensive care unit after evidence of multiple organ failure (coma, shock, acute respiratory distress syndrome, acute renal failure, etc.). However, initial parasitemia was less than 1%. The patient was managed by intravenous quinine and norepinephrine infusion due to refractory shock. The patient developed as an early complication ischemic lesions of both arms and feet. In addition to laboratory changes consistent with disseminated intravascular coagulation, there was also evidence for a low activity of the von Willebrand factor (VWF) cleaving protease ADAMTS13. Later complications included repeated candidemia and bacteraemia despite appropriate therapy; the origin appeared to be diffuse ischemic injury of the gastrointestinal tract. The patient ultimately recovered, but quadriamputation was necessary to treat symmetrical peripheral gangrene (SPG). In severe Plasmodium falciparum malaria, ischemic changes may be due to microvascular obstruction, but, in patients with low parasitemia, other endothelial factors may also be involved as observed in other groups of thrombotic microangiopathies.